Development of a Methodology for Fault Detection in Electrical Centralization Using Oriented Trees - Malovichko, N. V. (Science and Transport Progress, 2025)
Purpose. This work is aimed at reducing the time spent on locating failures in the station part of relay-type electrical centralization. Methodology. To achieve this goal, methods for searching for failures and the methods used to implement them were analyzed. It was found that due to the complexity of the process of determining the probability of failure for each element of the relay part of the centralization system, the failure detection methods currently in use are imperfect and ineffective. It is proposed to use failure detection algorithms in the form of directed trees, and the features of constructing directed graphs in the form of a tree are considered. Finding. A tree has been created for fault detection in the artificial sectioning of route sections, and its example illustrates ways to improve search algorithms by combining graphs for different faults into a common tree and using tree simplification by absorbing vertices. The possibilities of using Kruskal’s and Prim’s algorithms to determine the optimal search paths in a common tree are also presented. To solve this problem, the possibility of using Prufer’s code when displaying nodes and the weight of each edge of the tree in digital form is considered. Originality. For the first time, a methodology has been developed for determining the optimal paths for searching for failures in the post part of electrical centralization using oriented trees, which allows reducing the time for localizing failures and justifying the detection of points for installing control sensors to create an automated control system. Practical value. Using the proposed method allows you to determine the optimal paths for finding faults, create a computer-based guide to speed up the work of an electrical engineer when searching for a fault, identify the locations for installing control sensors in the process of developing an automatic control system, and record the actual time spent by maintenance personnel on searching for faults.